Kuliah Kerja Nyata Sebagai Media Pengabdian dan Inovasi Sosial: Studi Pengalaman di Kelurahan Mekar sari dan Sumber rejo, Kota Balikpapan - Zulkifli Abdullah; Salshabilla Wahyu Anafi; Selvy Esa Agustina (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Community Service Program (KKN) organized by Mulawarman University serves as a medium of social engagement and innovation in Mekar Sari and Sumber Rejo Urban Villages, Balikpapan City. This program was conducted over 38 days (July 14–August 20, 2025) targeting community groups at the urban village level, including local government officials, community leaders, youth groups, housewives, students, and micro, small, and medium enterprises. The implementation adopted a participatory approach through needs assessment, Focus Group Discussions (FGD), direct mentoring of target groups, as well as participatory monitoring and evaluation. Each program was carried out in three stages: preparation, implementation, and evaluation. In Mekar Sari, the program focused on environmental management and population administration, such as the “eggs-for-waste” innovation, operational system of the waste bank, and updating population data. Meanwhile, in Sumber Rejo, the activities emphasized social empowerment and the utilization of local assets, including updating tourism information media for Kang Bejo, teaching at the Kang Bejo Learning Space, socializing the dangers of bullying, and beautifying the Toga Herbal Garden. The results showed that Mekar Sari prioritized environmental and administrative governance, while Sumber Rejo focused more on strengthening social, educational, and local asset management aspects. Thus, KKN plays a vital role in enhancing community participation, strengthening local capacity, and promoting sustainable community-based development in Kota Balikpapan.